The Role of Pentecostal Worship in Virtues Development - Agustinus Dermawan (Sekolah Tinggi Teologi Satyabhakti, Malang, 2023)
As the readers may already knew, this author grew up in Pentecostal tradition, and I know that one of the primary characteristics of Pentecostalism is worship. I agree with what Robert Mapes Anderson said,